The impact of iron deficiency and anaemia on exercise capacity and outcomes in patients with chronic heart failure. Results from the Studies Investigating Co-morbidities Aggravating Heart Failure. (15th February 2016) - Ebner, Nicole; Jankowska, Ewa A.; Ponikowski, Piotr; Lainscak, Mitja; Elsner, Sebastian; Sliziuk, Veronika; Steinbeck, Lisa; Kube, Jennifer; Bekfani, Tarek; Scherbakov, Nadja; Valentova, Miroslava; Sandek, Anja; et al.
Abstract: Anaemia and iron deficiency (ID) are important co-morbidities in patients with chronic heart failure (HF) and both may lead to reduced exercise capacity. Methods: We enrolled 331 out-patients with stable chronic HF (mean age: 64 ± 11 years, 17% female, left ventricular ejection fraction [LVEF] 35 ± 13%, body mass index [BMI] 28.5 ± 5.2 kg/m 2, New York Heart Association [NYHA] class 2.2 ± 0.7, chronic kidney disease 35%, glomerular filtration rate 61.7 ± 20.1 mL/min). Anaemia was defined according to World Health Organization criteria (haemoglobin [Hb] < 13 g/dL in men, < 12 g/dL in women). ID was defined as serum ferritin < 100 μg/L or ferritin < 300 μg/L with transferrin saturation (TSAT) < 20%. Exercise capacity was assessed as peak oxygen consumption (peak VO2 ) by spiroergometry and 6-minute walk test (6MWT). Results: A total of 91 (27%) patients died from any cause during a mean follow-up of 18 months. At baseline, 98 (30%) patients presented with anaemia and 149 (45%) patients presented with ID. We observed a significant reduction in exercise capacity in parallel to decreasing Hb levels (r = 0.24, p < 0.001). In patients with anaemia and ID (n = 63, 19%), exercise capacity was significantly lower than in patients with ID or anaemia only. Cox regression analysis showed that after adjusting for NYHA, age, hsCRP and creatinine anaemia is an independent predictor of mortality in patients with HF (hazard ratio [HR]: 0.56, 95% confidence interval [CI]: 0.33–0.97, p = 0.04). Conclusion: The impact of anaemia on reduced exercise capacity and on mortality is stronger than that of ID. Anaemia remained an independent predictor of death after adjusting for clinically relevant variables.